Finansowe instrumenty zabezpieczające w księgach rachunkowych - Krzeszowski, Wojciech Dawid (Financial Hedging Instruments in the Accounting Books, 2005)
Financial hedging instruments can be used as a method of limiting the risk of business operations. The use of such instruments requires their recording in the accounting books. Issues related to the above are discussed in the following article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 271-276